14-240/Tutorial-December 2: Difference between revisions
From Drorbn
Jump to navigationJump to search
(8 intermediate revisions by 2 users not shown) | |||
Line 5: | Line 5: | ||
====Theorem==== |
====Theorem==== |
||
Let <math>A</math> be a <math>n \times n</math> matrix and <math>B</math> be the matrix <math>A</math> with two rows interchanged. Then <math>det(A) = -det(B)</math>. |
Let <math>A</math> be a <math>n \times n</math> matrix and <math>B</math> be the matrix <math>A</math> with two rows interchanged. Then <math>det(A) = -det(B)</math>. Boris decided to prove the following lemma first: |
||
Boris decided to prove the following lemma first: |
|||
=====Lemma 1===== |
=====Lemma 1===== |
||
Line 16: | Line 12: | ||
All we need to show is that <math>det(A) + det(B) = 0</math>. Assume that <math>B</math> is the matrix <math>A</math> with |
All we need to show is that <math>det(A) + det(B) = 0</math>. Assume that <math>B</math> is the matrix <math>A</math> with rows <math>i, i + 1</math> of <math>A</math> interchanged. Since the determinant of a matrix with two identical rows is <math>0</math>, then: |
||
Line 22: | Line 18: | ||
:::::::<math> |
:::::::<math>det\begin{pmatrix}...\\A_i\\A_{i + 1}\\...\end{pmatrix} + det\begin{pmatrix}...\\A_{i + 1}\\A_i\\...\end{pmatrix} =</math> |
||
:::::::<math>det\begin{pmatrix}...\\A_i\\A_i\\...\end{pmatrix} + det\begin{pmatrix}...\\A_i\\A_{i + 1}\\...\end{pmatrix} + det\begin{pmatrix}...\\A_{i + 1}\\A_{i + 1}\\...\end{pmatrix} + det\begin{pmatrix}...\\A_{i + 1}\\A_i\\...\end{pmatrix}</math>. |
:::::::<math>det\begin{pmatrix}...\\A_i\\A_i\\...\end{pmatrix} + det\begin{pmatrix}...\\A_i\\A_{i + 1}\\...\end{pmatrix} + det\begin{pmatrix}...\\A_{i + 1}\\A_{i + 1}\\...\end{pmatrix} + det\begin{pmatrix}...\\A_{i + 1}\\A_i\\...\end{pmatrix}</math>. |
||
Line 34: | Line 31: | ||
:::::::<math>det\begin{pmatrix}...\\A_i\\A_i\\...\end{pmatrix} + det\begin{pmatrix}...\\A_i\\A_{i + 1}\\...\end{pmatrix} + det\begin{pmatrix}...\\A_{i + 1}\\A_{i + 1}\\...\end{pmatrix} + det\begin{pmatrix}...\\A_{i + 1}\\A_i\\...\end{pmatrix} = </math> |
:::::::<math>det\begin{pmatrix}...\\A_i\\A_i\\...\end{pmatrix} + det\begin{pmatrix}...\\A_i\\A_{i + 1}\\...\end{pmatrix} + det\begin{pmatrix}...\\A_{i + 1}\\A_{i + 1}\\...\end{pmatrix} + det\begin{pmatrix}...\\A_{i + 1}\\A_i\\...\end{pmatrix} = </math> |
||
:::::::<math>det\begin{pmatrix}...\\A_i\\A_i + A_{i + 1}\\...\end{pmatrix} + det\begin{pmatrix}...\\A_{i + 1}\\A_i + A_{i + 1}\\...\end{pmatrix} = det\begin{pmatrix}...\\A_i + A_{i + 1}\\A_i + A_{i + 1}\\...\end{pmatrix} = 0</math>. |
:::::::<math>det\begin{pmatrix}...\\A_i\\A_i + A_{i + 1}\\...\end{pmatrix} + det\begin{pmatrix}...\\A_{i + 1}\\A_i + A_{i + 1}\\...\end{pmatrix} = det\begin{pmatrix}...\\A_i + A_{i + 1}\\A_i + A_{i + 1}\\...\end{pmatrix} = 0</math>. |
||
Then <math>det(A) + det(B) = 0</math> and <math>det(A) = -det(B)</math>. |
Then <math>det(A) + det(B) = 0</math> and <math>det(A) = -det(B)</math>. The proof of the lemma is complete. |
||
For the proof of the theorem, assume that <math>B</math> is the matrix <math>A</math> with rows <math>i, j</math> of <math>A</math> interchanged and <math>i \neq j</math>. By '''Lemma 1''', we have the following: |
|||
:::::::<math>det(A) =</math> |
|||
:::::::<math>det\begin{pmatrix}...\\A_i\\A_{i + 1}\\...\\A_j\\...\end{pmatrix} = (-1)det\begin{pmatrix}...\\A_{i + 1}\\A_i\\...\\A_j\\...\end{pmatrix} = (-1)^{j - i}det\begin{pmatrix}...\\A_{i + 1}\\...\\A_j\\A_i\\...\end{pmatrix} =</math> |
|||
:::::::<math>(-1)^{j - i}(-1)^{j - i - 1}det\begin{pmatrix}...\\A_j\\A_{i + 1}\\...\\A_i\\...\end{pmatrix} = (-1)^{2(j - i) - 1}det\begin{pmatrix}...\\A_j\\A_{i + 1}\\...\\A_i\\...\end{pmatrix} =</math> |
|||
:::::::<math>(-1)^{- 1}det\begin{pmatrix}...\\A_j\\A_{i + 1}\\...\\A_i\\...\end{pmatrix} = (-1)det\begin{pmatrix}...\\A_j\\A_{i + 1}\\...\\A_i\\...\end{pmatrix} =</math> |
|||
:::::::<math>-det(B)</math>. |
|||
Then the proof of the theorem is complete. |
|||
==Nikita== |
==Nikita== |
||
==Scanned Tutorial Notes by [[User Boyang.wu|Boyang.wu]]== |
|||
[[File:Tut.pdf]] |
Latest revision as of 11:55, 9 December 2014
|
Boris
Theorem
Let be a matrix and be the matrix with two rows interchanged. Then . Boris decided to prove the following lemma first:
Lemma 1
Let be a matrix and be the matrix with two adjacent rows interchanged. Then .
All we need to show is that . Assume that is the matrix with rows of interchanged. Since the determinant of a matrix with two identical rows is , then:
- .
Since the determinant is linear in each row, then we continue where we left off:
- .
Then and . The proof of the lemma is complete.
For the proof of the theorem, assume that is the matrix with rows of interchanged and . By Lemma 1, we have the following:
- .
Then the proof of the theorem is complete.